2021
DOI: 10.1158/2326-6066.cir-21-0111
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Immune Memory and Effector Activity to Cancer-Expressed MHC Class I Phosphopeptides Differ in Healthy Donors and Ovarian Cancer Patients

Abstract: Elevated immunity to cancer-expressed antigens can be detected in people with no history of cancer and may contribute to cancer prevention. We have previously reported that MHC-restricted phosphopeptides are cancer-expressed antigens and targets of immune recognition. However, the extent to which this immunity reflects prior or ongoing phosphopeptide exposures was not investigated. In this study, we found that preexisting immune memory to cancer-expressed phosphopeptides was evident in most healthy donors, but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…1E), we found previously undescribed phosphopeptides pGTF3C2, pPPP1R12A, pPIM1, pMYBBP1A, and pSRRM1 were presented by multiple EBV-BLCL and EBV-LPD, but not healthy B cells. Since some phosphopeptides have been shown to be immunogenic in A2+ donors[10,17,34], we sought to determine if A11+ donors also harbor phosphopeptide-specific T cells. We selected phosphopeptides and normal peptides presented by donor AP’s EBV-BLCL, and found that only pGTF3C2 elicited peptide- specific IFNg production by sensitized T cells from this donor (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1E), we found previously undescribed phosphopeptides pGTF3C2, pPPP1R12A, pPIM1, pMYBBP1A, and pSRRM1 were presented by multiple EBV-BLCL and EBV-LPD, but not healthy B cells. Since some phosphopeptides have been shown to be immunogenic in A2+ donors[10,17,34], we sought to determine if A11+ donors also harbor phosphopeptide-specific T cells. We selected phosphopeptides and normal peptides presented by donor AP’s EBV-BLCL, and found that only pGTF3C2 elicited peptide- specific IFNg production by sensitized T cells from this donor (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphopeptides represent an emerging class of HLA ligands that have potential to be targeted as shared tumor antigens produced not by mutations, but by cancer associated post-translational modifications. Since T cell responses to phosphopeptides have been studied comprehensively in the context of HLA-A*02:01 and -B*07:02 [10,34,42], we sought to expand the phosphopeptidome by systematically reanalyzing large immunopeptidomics datasets containing phosphopeptides, yielding a new set of phosphopeptides presented by the HLA-A3 supertype as well as C*07:01. We further used healthy tissue databases [40] to determine the extent to which these phosphopeptides are found on healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation